THE DISSOLUTION AND DIFFUSION OF FUROSEMIDE ON SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) - iis - wahyuningsih; Sugiyanto Sugiyanto; Ag. Yuswanto; Ronny Martien (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
Furosemide a diuretic exhibits low solubility in water and low bioavailability. The purpose of this study was to determine the effect SNEDDS formation to dissolution and diffusion of furosemide. SNEDDS was made with a mixture of 66% tween 80, 26% propylene glycol, 8% oleic acid and furosemide 40mg/mL. Test for SNEDDS dissolution of the capsules was developed using USP dissolution apparatus I and compared to market products, furosemide suspenssion and furosemide powder. The medium consists of 900mL of Artificial Gastric Fluid (AGF) , phosphate buffer pH 5.8 at 37±0.5°C and stirred with a speed of 100rpm. Diffusion test of SNEDDS furosemide was conducted by using reversed rat intestinal bowel and compared to furosemide suspension and furosemide solution. The SNEDDS formulation could enhance the dissolution and diffusion of furosemide compared to the non-SNEDDS formulation